Addressing challenges during community based screening of women for polycystic ovary syndrome (PCOS): A research experience from Maharashtra, India before and during COVID pandemic - Gazala Hasan; Sharmeen Shaikh; Beena Joshi; Mohd A Ganie; Amlin Shukla; Himali Vadhan; Rita Parab; Pravin Sanap; Iranna Mashal (Wolters Kluwer Medknow Publications, 2023)
Introduction: A multicentric community-based screening to determine prevalence of Polycystic Ovary Syndrome was undertaken in India. This article aims to describe the challenges faced at one site and strategies adopted to mitigate them. Material and Methods: Eligible women were enrolled at household-level and investigated for Polycystic Ovary Syndrome diagnosis as per Rotterdam criteria. Challenges faced were documented and alternate strategies were adopted. Results: Challenges ranged from identifying women as per the polling booth list, enrolling them, and getting them investigated. COVID-19 pandemic added to the challenges. Involving health system workforce, gaining community support, flexible timings, and alternate strategies for investigation including COVID-19 appropriate safety measures helped mitigate some of the challenges. Conclusion: Unforeseen challenges may crop up in community-based studies, like the ones faced during the COVID-19 pandemic. Planning, strategizing, using technology to keep communications on, and finding out of the box and amicable solutions for bottlenecks may help mitigate challenges.